O Feminismo Negro e as Reformas Curriculares Latino-Americana no Currículo de Matemática da Educação Tecnológica Profissional - Araújo Ribeiro de Castro, Josicléia (2023)
Comparative Education can be perceived as an episteme of search for understanding the way educational systems develop, configuring itself as a conceptual and methodological perspective to approach educational phenomena from an international, supranational or intranational perspective, through analysis of the discourses that involve them. In this sense, this comparative study, constituent of the research agenda of the Interdisciplinary Center for Advanced Research in Curriculum (Nipac), has as general objective: To discuss the mathematics curriculum in the curricular development of professional education in Latin American countries that have undergone curricular reforms in the last three decades (Brazil, Chile and Peru), characterizing, in these reforms, the conception of the public sphere undertaken in the construction of these curricula, the theoretical aspects that substantiate them, and the rationalities that underlie these processes, emphasizing the provision of ethnic-racial issues.Therefore, this investigation is philosophically and methodologically based on the framework of Jürgen Habermas, mainly on the theoretical contributions of the concepts of public sphere and discursive ethics; In Nancy Fraser for the understanding of the device of redistribution and social justice, going through the contributions of black feminism to the strengthening of social movements and the redemocratization of spaces of power and knowledge, analyzing mathematics curricula of three countries that, historically, undergo curricular reforms: Brazil, Chile and Peru, and in the case of Brazil, to perceive the struggle and the anti-racist theorization, in the construction of the mathematics curriculum. The constitution of the data involves bibliographic analyses, documentary analyses, interviews, and technical visits to the countries investigated.